PENILAIAN KINERJA SAHAM PADA PELAKSANAAN IPO DITINJAU DARI UNDERPRICING DAN MARKET OVERREACTION - Kusuma, Desta Rizky (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2012)
This study aims to determine the short-term and long-term stock performance after the IPO and market overreaction symptoms in IDX. In terms of performance shares underprice stocks, short-term performance share is calculated one month after the IPO and long-term calculated six months after the IPO. The data sample are firms listed on the IDX of IPOs in the year 2000 - 2007, obtaining a sample of 102 firms. Based on the analysis, the short-term stock performance post-IPO can provide a positive abnormal return and long stock performance post-IPO will go down or decline (long run underperformance). The results showed no symptoms of market overreaction, because there is no relationship in the opposite pattern of abnormal returns earned on short-term and long term.